Noninvasive respiratory support via nasal cannula in premature infants: Is it really safe? - Büyüktiryaki, Mehmet; Okur, Nilüfer; Kadıoğlu-Şimşek, Gülsüm; Kanmaz, Hayriye Gözde; Canpolat, Fuat Emre (The Turkish Journal of Pediatrics, 2019)
With this observational study we attempted to assess whether nasal cannulas originally used to administer high flow could be effectively used as an interface to provide ventilator generated noninvasive respiratory support. Preterm infants whose gestational ages between 26 < sup > 0/7 < /sup > and 29 < sup > 6/7 < /sup > weeks with respiratory instability who initially received noninvasive respiratory support with binasal prongs and then switched to nasal cannula with attending physician`s decision were included. Six infants (27%) needed intubation and mechanical ventilation while getting noninvasive support via nasal cannula, whereas this was not observed during noninvasive ventilation via short binasal prongs (p=0.02). Despite the nasal cannula being easy to use and well tolerated by the preterm infant, it is not as effective as the short binasal prong when it is used as an interface in a mechanical ventilator that provides noninvasive respiratory support other than its own equipment.